Biodegradable and Dual‐Responsive Polypeptide‐Shelled Cyclodextrin‐Containers for Intracellular Delivery of Membrane‐Impermeable Cargo. Issue 18 (18th July 2021) - Kudruk, Sergej; Pottanam Chali, Sharafudheen; Linard Matos, Anna Livia; Bourque, Cole; Dunker, Clara; Gatsogiannis, Christos; Ravoo, Bart Jan; Gerke, Volker
Abstract: The transport of membrane impermeable compounds into cells is a prerequisite for the efficient cellular delivery of hydrophilic and amphiphilic compounds and drugs. Transport into the cell's cytosolic compartment should ideally be controllable and it should involve biologically compatible and degradable vehicles. Addressing these challenges, nanocontainers based on cyclodextrin amphiphiles that are stabilized by a biodegradable peptide shell are developed and their potential to deliver fluorescently labeled cargo into human cells is analyzed. Host–guest mediated self‐assembly of a thiol‐containing short peptide or a cystamine‐cross‐linked polypeptide shell on cyclodextrin vesicles produce short peptide‐shelled (SPSVss ) or polypeptide‐shelled vesicles (PPSVss ), respectively, with redox‐responsive and biodegradable features. Whereas SPSVss are permeable and less stable, PPSVss effectively encapsulate cargo and show a strictly regulated release of membrane impermeable cargo triggered by either reducing conditions or peptidase treatment. Live cell experiments reveal that the novel PPSVSS are readily internalized by primary human endothelial cells (human umbilical vein endothelial cells) and cervical cancer cells and that the reductive microenvironment of the cells' endosomes trigger release of the hydrophilic cargo into the cytosol. Thus, PPSVSS represent a highly efficient, biodegradable, and tunable system for overcoming the plasma membrane as a natural barrier for membrane‐impermeable cargo. Abstract : Transport of membrane impermeable compounds into the cell's cytosolic compartment should ideally be controllable and involve biologically compatible and degradable vehicles. Addressing these challenges, nanocontainers based on cyclodextrin amphiphiles that are stabilized by a biodegradable peptide shell are developed and their potential to deliver fluorescently labeled or biological active cargo into human cells is shown.